La preparación física en la disciplina del baloncesto y su repercusión en el desarrollo de las capacidades físicas y motoras en los alumnos de los centros educativos de la parroquia de Vilcabamba, perteneciente al cantón Loja - Naranjo Abarca, Dario Javier (2013)
This thesis refers to " THE PHYSICAL TRAINING IN THE COURSE OF BASKETBALL AND ITS IMPACT ON THE DEVELOPMENT OF PHYSICAL AND MOTOR CAPACITY IN STUDENTS OF SCHOOLS OF THE PARISH Vilcabamba , Loja BELONGING TO CANTON " .The population for this research analyze consists of student colleges " Vilcabamba and Juan Montalvo " parish of Vilcabamba.This research is one way to assess the level of physical preparation they receive in basketball discipline students in schools in the parish of Vilcabamba and their relationship in the development of their physical and motor skills. To do this, different methods among which are the Scientific, Inductive- Deductive, Descriptive, Analytic - Synthetic, Statistical methods that allowed for discussion and comparison of the proposed variables and used the same techniques and instruments are used as survey, observation , interviews , questionnaires and test that allowed them to obtain optimum results to determine their impact on the development of physical and motor skills physical training in the discipline of basketball.